Halaqah Kitab Kuning (Nahwu Sharaf) di Pambusuang Balanipa Polewali Mandar Sulawesi Barat / Halaqah Kitab Kuning (Nahwu Sharaf) in Pambusuang Balanipa Polewali Mandar West Sulawesi - Khaerun Nisa Nuur; Laely Yuliani Said (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
ﻳرتكز هذا البحث في حلقة الكتب التراثية (النحو و الصرف) في قرية بانبوسووانغ منطقة بالانيفا مقطعة بوليوالي ماندار في "تعليم أوائي" باجراء البحث المتعلق بالطريقة المستخدمة في تلك الحلقة مع إشكالياتها. هذا البحث وصفي نوعي، والبيانات التي تم الحصول عليها مأخوذة من البيانات الأولية والبيانات الثانوية، وجمع البيانات عن طريق الملاحظة والمقابلة والتوثيق وتحليلها عن طريق صفي. النتائج التي تم الحصول عليها في هذا البحث هي أن حلقة الكتب التراثية (النحو والصرف) في قرية بانبوسووانغ نشأت من تعليم الكتب باسم "تعليم أوائي " الذي اسسه الشخصي الديني اسمه "عبد الشهيد رشيد" المشهور بـأنانغ غورو شهيد “Annangguru Syahid”. تتكون الطريقة المستخدمة في التعليم من ثلاث مستويات وهي: ١) الصرف جالابو، ٢)  النحو المعلق، ٣)  الكتب الصرفية والنحوية وجميعها تتلخص في نهج: الحفظ والتلقي والجماعة ومهارة الاستماع والملاحظة وإعطاء الأمثلة والأساليب الكلاسيكية والمعاصرة و طرق الصرف جالافو و النحو المعلق و الإعراب.الكلمات المفتاحية : كتب النحو و الصرف; بانبوسووانغAbstract:This study examined the Halaqah Kitab Kuning in Pambusuang Village, Balanipa Subdistrict, Polewali Mandar Regency in “Uwae Study” by conducting searches related to the methods used in the Halaqah and its problems. This research is a descriptive qualitative method in which the data obtained is sourced from primary data and secondary data. Data collection was conducted through observation, interview, documentation, and analysis descriptively. The results obtained in this study is Halaqah Kitab Kuning in Pambusuang Village started from the study of a book called "Uwae Study", which was founded by a religious figure named Abd. Shahid Rashid, known as "Annangguru Syahid". The study of that book until now become a study of the Kitab Kuning (Nahwu Sharaf). The methods used in the study consists of three levels: a) Sharaf Galappo, b) Nahwu Gantung, and c) The Kitab Kuning, which then summarized in the methods: memorization, Talaqqi, grouping, and listening and giving examples, classical and contemporary methods, Nahwu Gantung and Sharaf Galappo methods, and I'rab methods.